Zinc/CaMK II Associated-Mitophagy Signaling Contributed to Hippocampal Mossy Fiber Sprouting and Cognitive Deficits Following Neonatal Seizures and Its Regulation by Chronic Leptin Treatment - Li, Li-li; Jin, Mei-fang; Ni, Hong (Frontiers in Neurology, 2018)
The role of leptin in the pathogenesis of epilepsy is receiving more attention in clinical and basic research. Although there are data indicating the neuroprotective effects of elevated serum / brain leptin levels following acute seizures, no study to date has examined the impact of chronic leptin treatment on long-term brain injury following developmental seizures. The aim of this study was to evaluate whether chronic leptin treatment has neuroprotective effects on cognition as well as hippocampal mossy fiber sprouting following flurothyl-induced recurrent neonatal seizures and whether these effects are mediated by the zinc/CaMKII-associated mitophagy signaling pathway. Forty Sprague-Dawley rats (postnatal day 6, P6) were randomly assigned to two groups: the neonatal seizure group and the control group. At P13, the rats were further divided into the control group, seizure group (RS), control + leptin (leptin, i.p., 2 mg / kg / day for 10 days), seizure+leptin group (RS+Leptin, 2 mg/kg/day, i.p., for 10 consecutive days). The Morris water maze test was performed during the period from P27-P32. Subsequently, Timm staining and Western blotting were used to detect the mossy fiber sprouting and the protein levels in the hippocampus, respectively. The flurothyl-induced seizures (RS group) significantly down-regulated the mitophagy markers PINK, Drp1, and PHB, as well as the memory marker CaMKII alpha, while up-regulating the zinc transporters ZnT3, ZnT4, and ZIP7, as well as the autophagy execution molecule cathepsin-E. These findings paralleled the findings of hippocampal aberrant mossy fiber sprouting and cognitive dysfunction. However, these changes were restored with chronic leptin treatment (RS+Leptin group). The results showed that leptin had a neuroprotective effect on the hippocampal pathological damage and on cognitive deficits induced by neonatal seizures and suggested that the Zinc/CaMKII associated-mitophagy signaling pathway in the hippocampus may be a novel target for leptin neuroprotection, with potential value in translational medicine.